Mitochondrial Encephalopathy and Cytochrome C - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Benefits from treatment of mitochondrial encephalomyopathy (MEM) with cytochrome C (6.25 mg) and vitamins Bl (25 mg) and B2 (12.5 mg), in daily injections, are reported from Osaka University Medical School and other centers in Japan.